Construção e validação de checklist sobre fatores de risco para lesão por pressão - Teles, Maria Josiene Menezes (2019)
The construction and validation of a Checklist on risk factors for Pressure Injury is an important working tool in the evaluation of these factors by the nurse, as it assists in the systematic, effective and safe clinical judgment for the quality of Nursing care and the consequent decrease of the incidence of this lesion. Objective: to construct and validate a research tool, in the form of a Checklist, on risk factors for the development of Pressure Injury, in the critical patient. Method: This is a methodological study of quantitative approach. The instrument was developed from the Guideline for Pressure Ulcer Prevention and Treatment, the Pressure Ulcer Prevention Protocol, the Norton, Waterlow and Braden structured scales and the authors' clinical experience. We used the Pasquali Psychometric Model for validation. The analysis of the data was done through the Percentage of Agreement between the judges and the Content Validity Index. Results: In the first evaluation of the instrument, the criteria consistency and objectivity reached agreement of 97% and 98% respectively and all items of these criteria reached an index of validity superior to 80%. The clarity criterion obtained 79.29% agreement and content 87.43%, but seven items of these criteria did not obtain a validity index equal to or greater than 80%, which implied a reformulation of the Checklist. After reformulation of these items and the second evaluation, absolute agreement (100%) was obtained. Conclusion: The instrument was validated and can subsidize the quality and safety of the patient in the prevention of pressure injury.